2022
DOI: 10.20485/jsaeijae.13.2_38
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Soot Trapping Process and Manufacturing of Three-Way Catalyzed Membrane Filter

Abstract: Soot trapping on GPF, TWC Membrane fabrication on GPF, and soot trapping on TWC membrane have been studied using computer numerical simulation. The results of pressure drop, filtration efficiency, and morphology visualization satisfied the experimental results. The simulation could clarify the trapping phenomena up to 3D-nanoscale resolution, which overcame an experimental limitation. Visualization revealed the particles first trapped on the substrate generating a dendrite structure at the constricted area. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A previous study showed a drastic increase in pressure drop during membrane fabrication on a conventional particulate filter. This occurred in the bridging and pore deposition phases, similar to soot trapping behavior [ 5 , 7 , 8 ]. As a result, it reflects that a conventional GPF is not the best-optimized support for a membrane filter.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…A previous study showed a drastic increase in pressure drop during membrane fabrication on a conventional particulate filter. This occurred in the bridging and pore deposition phases, similar to soot trapping behavior [ 5 , 7 , 8 ]. As a result, it reflects that a conventional GPF is not the best-optimized support for a membrane filter.…”
Section: Introductionmentioning
confidence: 85%
“…Simulations of membrane fabrication and soot trapping conducted in this study followed a previous study [ 5 ]. Generally, each simulation involves several filtration iterations.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations